Kajian Atas Buku Pantun Melayu: Titik Temu Islam dan Budaya Lokal Nusantara Karya Abd. Rachman Abror (Pendekatan Filologi) - Indasari, Nofi Fitria; Mugni, Mugni (Indo-MathEdu Intellectuals Journal, 2024)
This research was written based on the results of research on the study of the book Malay Poetry: The Meeting Point of Islam and Local Culture of the Archipelago by Abd. Rahman Abror. This study aims to find out the meaning of philology, to find out the approaches, methods, techniques, steps and research results in the book Malay Poetry: The Convergence of Islam and Local Culture of the Archipelago by Abd. Rahman Abror. The research method used in this study is a qualitative method in the form of literature study research with a philological approach. The source of data is in the form of a Malay Poetry Book by Abd. Rahman Abror. The data analysis technique is carried out by way the data is classified in the following steps, the data is described in its entirety. The results of the study showed that the number of rhymes memorized by the conductor and successfully recorded by Abd. Rahman Abror is 1,185 poems from 8 people who memorize poems. However, the poems were selected again so that the number became 815 poems. To get the expected results, all the poems that have been recorded by Abd. Rahman Abror is written in the form of text. In the book Pantun Melayu: Temu Temu Islam and local culture of the archipelago by Abd. Rahman Abror whose study discusses the concepts of poetry and Islamic values related to the social and cultural life of the Pontianak Malay ethnicity, where the two concepts are not independent but interconnected